PENGARUH CITRA MEREK, LOKASI, DAN PROMOSI TERHADAP LOYALITAS KONSUMEN MELALUI MINAT BELI ULANG SEBAGAI VARIABEL INTERVENING PADA DEALER HONDA JAYA TERANG III BESUKI - Izan Maulana; Randika Fandiyanto; Triska Dewi Pramitasari (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study aims to analyze the influence of brand image, location, and promotion on consumer loyalty with repurchase intention as an intervening variable at Honda Jaya Terang III Dealer in Besuki. The background of this research lies in the importance of understanding factors that can drive consumer loyalty, especially amidst the increasingly intense competition in the two-wheeler automotive industry. The research uses a quantitative approach with data collected through questionnaires distributed to customers who have made transactions at the dealer. Data analysis was conducted using the Partial Least Square (PLS) method through the SmartPLS application. The results indicate that brand image, location, and promotion have a positive and significant effect on repurchase intention, and indirectly affect consumer loyalty through repurchase intention. Repurchase intention is proven to be an effective intervening variable that strengthens the influence of independent variables on consumer loyalty. These findings can serve as a basis for the dealer's management to develop more effective marketing strategies to enhance customer loyalty.